Evaluasi Kepuasan Pelayanan Informasi Obat (PIO) Pada Pasien Rawat Jalan BPJS Dan Non-BPJS Di Instalasi Farmasi RSUD Dr. Moewardi - Sania Ari Rahmawati; Hanugrah Ardya; Agnes Prawistya Sari (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
The Drug Information Service is an activity conducted by pharmacists to provide patients with information about medications, including dosage, dosage form, administration route, safety of use, side effects, and drug interactions. This service is crucial for patients, particularly those lacking detailed information about their prescribed medications. This study aimed to assess the level of satisfaction with drug information services among outpatient patients with BPJS and non-BPJS insurance at the Pharmacy Department of Dr. Moewardi Regional Public Hospital. The research adopted a quantitative approach with a cross-sectional design. Data collection was conducted using a questionnaire with 100 respondents. The findings of the study indicated that across 5 dimensions of satisfaction, the distribution of respondent answers regarding satisfaction with drug information services at the Outpatient Pharmacy of Dr. Moewardi Regional Public Hospital showed the following: reliability dimension 67.85% in the category of fairly satisfied, responsiveness dimension 63.20% in the category of fairly satisfied, assurance dimension 66.33% in the category of fairly satisfied, empathy dimension 68.52% in the category of fairly satisfied, and tangibles dimension 63.7% in the category of fairly satisfied. BPJS prescription type received a satisfaction percentage of 66.20%, while non-BPJS received 64.74%. In conclusion, the overall satisfaction level with drug information services at the Outpatient Pharmacy of Dr. Moewardi Regional Public Hospital could be categorized as fairly satisfied.